Impact of the COVID-19 pandemic on children and adolescents: determinants and association with quality of life and mental health-a cross-sectional study - Viviane Richard; Roxane Dumont; Elsa Lorthe; Andrea Loizeau; Hélène Baysson; María-Eugenia Zaballa; Francesco Pennacchio; Rémy P. Barbe; Klara M. Posfay-Barbe; Idris Guessous; Silvia Stringhini; SEROCoV-KIDS Study Group (BMC, 2023)
Abstract Background The medium-term impact of the COVID-19 pandemic on the wellbeing of children and adolescents remains unclear. More than 2 years into the pandemic, we aimed to quantify the frequency and determinants of having been severely impacted by the COVID-19 pandemic and estimate its impact on health-related quality of life (HRQoL) and mental health. Methods Data was drawn from a population-based cohort of children and adolescents, recruited between December 2021 and June 2022, in Geneva, Switzerland. The Coronavirus impact scale was used to assess the multidimensional impact of the pandemic on children through parent's report. A score higher than one standard deviation above the mean was deemed a severe impact. Parents additionally reported about their offspring HRQoL and mental health with validated scales. Determinants of having been severely impacted were assessed with logistic models, as were the associations between having experienced a severe impact and poor HRQoL or mental health. Results Out of 2101 participants aged 2-17, 12.7% had experienced a severe pandemic impact. Having a lasting health condition, a pandemic-related worsening of lifestyle habits or an unfavorable family environment were associated with having been severely impacted by the pandemic, while a previous anti-SARS-CoV-2 infection was not. Participants who had experienced a severe pandemic impact were more likely to present poor HRQoL (aOR = 3.1; 95% CI 2.3-4.4) and poor mental health (aOR = 3.9; 95% CI 2.5-6.2). Conclusion The COVID-19 pandemic may have persistent consequences on the wellbeing of children and adolescents, especially among those with health and family vulnerabilities.